ENVIRONMENTAL RESPONSIBILITY MODEL BASED ON ISO 14000 MANAGEMENT SYSTEMS - Catalina SITNIKOV (Management & Marketing)
Worldwide corporations, as well as their stakeholders, are more conscious of the need for environmental management, SR behaviour, and sustainable growth and development. International Standards are becoming more significant for corporations to work towards common environmental management practices. ISO 14001 is the first and the broadest standard intended at a more responsible approach of corporations and the world’s most acknowledged framework for environmental management systems that assists corporations to better manage the effect of their activities on the environment. This article aims to study ISO 14001 implementation and its effects on the environmental responsibility. A model will be built, which covers the environmental management system, the components of organizational culture, being able to influence environmental standards implementation.